NÔ-TEATER SOM SCENISK VIRKELIGHED OG LITTERÆRT BLÆNDVÆRK - Flindt, Willie (Tidsskriftet Antropologi, 2000)
This article deals with the traditional Japanese Nô theatre focusing on the relation between illusion and reality. Three nô plays are retold: Tôru deals with the mortal obsession of an imitated landscape, Genji kuyô with fiction as delusion, and Kantan with a magic pillow as instrument of revelation. The notion of the material world as an illusion together with the concrete and physical staging are analysed as an interplay between scenic illusion and reality.